Manipulation of Soliton Bunches Generated From a Polarization-Route-Assisted Vector Fiber Laser - Zhichao Wu; Qian Wei; Bingye Zhan; Tianye Huang; Ming Zhu; Lu Li; Perry Ping Shum (IEEE Photonics Journal)
In this article, we report robust vector soliton bunches arising in a passively mode-locked fiber laser based on carbon nanotube (CNT). By introducing a polarization-route-assisted module (PRAM) and finely adjusting the cavity birefringence, the soliton bunches can be flexibly manipulated to operate with controllable soliton numbers and positions. Moreover, the potential bandwidth resource provided by the concept of soliton bunches for the ease of breaks a new path for the enhancement of data-carrying capacity. Our research is helpful to extend the theory of vector soliton dynamics in fiber lasers and promotes the promising application in optical communication systems.